An experimental investigation of a toroidal engine combustion chamber. - Quiros, Edwin N. (Philippine Engineering Journal)
An exploratory study of a toroidal engine combustion chamber using a constant volume bomb is reported in this paper. The toroidal shape design of the combustion chamber studied attempts to achieve continuous fresh air fresh fuel mixing during injection and obtain desirable rates of air circulation using injected fuel momentum and combustion energy by varying the cross sectional area of the combustion chamber. High speed photographs of the combustion event were taken for flow visualization. The pressure time histories of the combustion process was also obtained to characterize combustion and the effects of changes in combustion chamber dimensions, injector position, ignition source and charge density and temperature. Preliminary results of the experiments undertaken are described.